Integrating color centers in silicon to optical microcavities: towards building a novel integrated quantum photonic device. - Kizhake Veetil, Vijin (My University, 2024)
Fluorescent defect centers in silicon have been studied extensively for the last 50 years. Recently, they have attracted considerable attention for quantum-information applications, both as single-photon sources and for interfacing stationary qubits with photons—essential components for quantum networking and multiprocessor quantum computing. If silicon can host suitable luminescent defects for quantum photonic technologies, the development of those technologies would be greatly accelerated by leveraging this highly developed material platform. A major work highlighting several luminescent defects in silicon that can be useful for achieving this goal was published in a review article by Davies in 1989.\indent In this work, we are particularly interested in looking at two types of defects in silicon called W and G centers. They have emissions in the near-infrared wavelength, eliminating the need for frequency conversion techniques to utilize the low propagation loss bands in optical fibers. However, their measured photon count rate is low because of the poor extraction of emission from the host semiconductor due to the high refractive index of silicon. Therefore, for luminescent defects in silicon to serve as useful single-photon sources for quantum photonics, emitted photons must be efficiently extracted from the silicon host and funneled into a useful optical spatial mode (e.g., a low-diffraction Gaussian beam or an on-chip waveguide mode). This can be achieved by leveraging cavity quantum electrodynamics (cavity QED) effects, where the emitter is placed in a microscopic optical cavity designed to support optical resonances. \indent Here, we increase the photon collection efficiency from an ensemble of W centers by embedding them in circular Bragg grating (CBG) cavities resonant with their zero-phonon-line emission. CBG cavities offer high extraction efficiency into a near-Gaussian free-space beam with relatively small divergence and a modest Purcell radiative rate enhancement. We also demonstrate a polarized emission from open-ended CBG cavities called bowtie cavities, with a comparable Purcell factor and collection enhancement. Bowtie cavities provide straightforward, direct optical and electrical access to embedded color centers from their open ends and, therefore, may provide advantages in devices where capabilities, such as current injection or waveguided resonant optical excitation, are desired. These devices can have potential applications in quantum communication, quantum computation, etc, in large-scale quantum networks.